Jane Austen’s Pride and Prejudice: A Social Comedy - Priydarshi, Ashok Kumar (Journal of Advanced Research in English & Education; Vol 10 No 2 (2025): Journal of Advanced Research in English and Education, 2025)
Jane Austen’s Pride and Prejudice is a masterpiece of English literature, widely celebrated not only for its enduring romance but also for its brilliant depiction of society as a social comedy. This article explores the multifaceted ways in which Austen utilizes comedy to critique and illuminate the social mores, class distinctions, and gender roles of the late 18th and early 19th centuries. We will delve into the novel’s satirical wit, which exposes the absurdities of the marriage market, the hypocrisy of the gentry, and the foibles of human nature. The comic elements, ranging from witty dialogue to farcical character portrayals, serve a dual purpose: they entertain the reader while simultaneously providing a sharp social critique. This analysis will examine how characters such as Mr. Collins, Lady Catherine de Bourgh, and Mrs. Bennet function as satirical figures, embodying the ridiculousness of social climbing and superficiality. Furthermore, the article will discuss how the central romantic plot between Elizabeth Bennet and Fitzwilliam Darcy, while often seen as the heart of the novel, is itself a vehicle for exploring the comedic misunderstandings and ironies inherent in social interactions. By dissecting the novel’s comedic strategies, this paper argues that the designation of Pride and Prejudice as a “social comedy” is not merely an aesthetic label but a key to understanding its profound thematic depth and its lasting relevance as a commentary on human pride and social prejudice.